Low Back Pain and Sciatica Related with the Premenstrual Period in Patients with Lumbar Disc Herniation - Akgun, Bekir; Kaplan, Metin; Arici, Lutfu; Pusat, Serhat; Erol, Fatih Serhat (Turkish Neurosurgical Soc, 2010)
AIM: We examined the clinical progress of low back pain and radicular pain during the premenstrual period in patients with lumbar disc protrusion and discussed the probable effective physiopathological mechanisms and laboratory results reported in the literature. MATERIAL and METHODS: Fifty female patients with complaints of low back and leg pain, and with lumbar disc protrusion in their MRI investigations were included in the study. The pain was assessed using the modified Low Back Outcome Scale of Greenough and Fraser in the premenstrual and the normal postmenstrual periods. RESULTS: There was an increase in the use of analgesic drugs and the need for rest during the premenstrual period (p<0.05). The severity of pain was significantly different between the two periods and it was more severe at the premenstrual period (p<0.05). CONCLUSION: All the criteria that we chose from the modified Low Back Outcome Scale of Greenough and Fraser to assess the pain showed a significant difference between the premenstrual period and the normal period in our patients. This difference should be considered in the treatment strategies in the clinical setting. Patients should be re-evaluated for surgical decisions after the premenstrual period if possible.
lomber disk herniasyonlu hastalarda premenstruel periyod ile i?li?ki?li? bel ve bacak a?rısı
Keywords: Lumbar disc herniation; Low back pain; Premenstrual period; Sciatica